Understanding progressive failure mechanisms of a wind turbine blade trailing edge section through subcomponent tests and nonlinear FE analysis. (15th April 2019) - Chen, Xiao; Berring, Peter; Madsen, Steen Hjelm; Branner, Kim; Semenov, Sergei
Abstract: This paper presents a comprehensive study on structural failure of a trailing edge section cut from a composite wind turbine blade. The focus is placed on understanding progressive failure behavior of the trailing edge section in subcomponent testing during its entire failure sequence. Digital Image Correlation (DIC) is used to capture buckling deformation and strain distributions of the specimen. Detailed post-test inspection is performed to identify failure modes and failure characteristics. A nonlinear Finite Element (FE) model that accounts for all observed failure modes is developed based on continuum damage mechanics and progressive failure analysis techniques. Multiple structural nonlinearities due to buckling, contact and material failures are included in the model to predict the failure process. The study shows that in addition to the buckling-driven failure phenomenon, the surface contact of sandwich panels contributes to the failure process of the trailing edge section. Foam materials start to fail before the ultimate load-carrying capacity of the specimen is reached, while both composite materials and adhesive materials fail in the post-peak regime. The matrix-dominant failure and delamination develop before the fiber-dominant failure in composite laminates. The proposed FE model captures the progressive failure process of the trailing edge section reasonably well.